2000
DOI: 10.1177/1081180x00005001005
|View full text |Cite
|
Sign up to set email alerts
|

Social Access to the Internet

Abstract: The relative costs and expertise associated with using the Internet, labeled technological and social access, have led to a concern about the rise of a “digital divide” between information haves and have-nots. To address whether and to what extent the Internet has become a medium of the masses and to identify the factors associated with social access to the Internet, I examine Internet use data from two statewide surveys, the Carolina Poll and the Indiana Poll, conducted during spring 1998. Multivariate analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
1
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 1 publication
4
100
1
8
Order By: Relevance
“…A general finding is that the development of the digital divide parallels that of economic inequality (e.g. Bucy, 2000;Luke, 2000;Attewell, 2001;Jung et al, 2001;Bonfadelli, 2002;Ekdahl and Trojer, 2002). Part of this discussion revolves around the diametric antipodes of a utopian versus dystopian view, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A general finding is that the development of the digital divide parallels that of economic inequality (e.g. Bucy, 2000;Luke, 2000;Attewell, 2001;Jung et al, 2001;Bonfadelli, 2002;Ekdahl and Trojer, 2002). Part of this discussion revolves around the diametric antipodes of a utopian versus dystopian view, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although a significant part of this debate concerns the wider global dimensions of the digital divide in Internet access and use (Yu 2006), national surveys have found that within national populations, there exist consistent age/ cohort differences (Akhter 2003;Bucy 2000;Chakraburty and Bosman 2005;Chaudhuri et al 2005;Cutler et al 2003;Loges and Jung 2001;Peacock and Künemund 2007;Silver 2001). Most of these reports interpret the lower rates of access to and use of the Internet by older adults as a reflection of the structural 'marginality' of older peopletheir relative poverty, lack of education, greater disability, and exclusion from the work-force-in short ''the crystallisation of existing socioeconomic inequalities…within the older population'' (Peacock and Künemund 2007 pp 191).…”
Section: Introductionmentioning
confidence: 99%
“…Another general finding is that the development of the digital divide parallels that of economic inequality (Bucy 2000;DiMaggio et al 2001;Korupp and Szydlik 2005;Korupp 2006). 3 In a typology of Internet users it is suggested that educational level enhances general levels of interest (Mollenkopf and Kaspar 2005).…”
mentioning
confidence: 99%